High-Performance Anti-freezing Flexible Zn-MnO2 Battery Based on Polyacrylamide/Graphene Oxide/Ethylene Glycol Gel Electrolyte - Quan, Yuhui; Chen, Minfeng; Zhou, Weijun; Tian, Qinghua; Chen, Jizhang (Frontiers in Chemistry, 2020)
It remains a great challenge for aqueous zinc-ion batteries to work at subzero temperatures, since the water in aqueous electrolytes would freeze and inhibit the transportation of electrolyte ions, inevitably leading to performance deterioration. In this work, we propose an anti-freezing gel electrolyte that contains polyacrylamide, graphene oxide, and ethylene glycol. The graphene oxide can not only enhance the mechanical properties of gel electrolyte but also help construct a three-dimensional macroporous network that facilitates ionic transport, while the ethylene glycol can improve freezing resistance. Due to the synergistic effect, the gel electrolyte exhibits high ionic conductivity (e.g., 14.9 mS cm−1 at −20 °C) and good mechanical properties in comparison with neat polyacrylamide gel electrolyte. Benefiting from that, the assembled flexible quasi-solid-state Zn-MnO2 battery exhibits good electrochemical durability and superior tolerance to extreme working conditions. This work provides new perspectives to develop flexible electrochemical energy storage devices with great environmental adaptability.